Analisis Kelayakan Penyajian Buku Teks Bahasa Indonesia Ekspres Diri dan Akademik Kelas XII Terbitan Kemendikbud 2015 - Nindya Juniarti; Fina Lailatul Fadhilah; Vira Shafina; Yuyun Yuyun; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Textbooks are one of the important media needed by students in the learning process. Referring to the accuracy, the author uses a quantitative research method with a focus on Content Analysis, which aims to determine the feasibility of presenting the text book, the object of this research is the Indonesian language textbook used by class XII students. The data can be described based on the analysis of Indonesian language textbooks in class XII that have been analyzed, so it can be concluded that the book has appropriate presentation techniques in BTBI including systematic consistency of presentation in chapters, has motivational generators at the beginning of chapters, has sample questions, in each chapter, has contains a strengthening of conceptual understanding and is given evidence of experimental results that can be copied in students' personal books, has a glossary, index, bibliography, and appendices. As well as the delivery of messages between sub-chapters and other chapters/sub-chapters with sub-chapters/between the lines in adjacent sub-chapters reflects the coherence and interrelationship of content and in one chapter the message or material presented already reflects the unity of the theme.